2003
DOI: 10.1186/1471-2407-3-28
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-steroidal anti-inflammatory drugs on cancer sites other than the colon and rectum: a meta-analysis

Abstract: Background: Observational studies have consistently shown that aspirin and non-steroidal antiinflammatory drug (NSAID) use is associated with a close to 50% reduced risk of colorectal cancer. Studies assessing the effects of NSAIDs on other cancers have shown conflicting results. Therefore, we conducted a meta-analysis to evaluate the relationship between NSAID use and cancer other than colorectal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
109
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(123 citation statements)
references
References 64 publications
12
109
1
1
Order By: Relevance
“…The other two studies found no effect (Egan et al, 1996;Anderson et al, 2002). The summary estimate for these studies is 0.78 (95% CI: 0.70, 0.86) (González-Pérez et al, 2003). As opposed to aspirin, long-term use of non-aspirin NSAIDs was not associated with a reduced risk of developing breast cancer in our study.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The other two studies found no effect (Egan et al, 1996;Anderson et al, 2002). The summary estimate for these studies is 0.78 (95% CI: 0.70, 0.86) (González-Pérez et al, 2003). As opposed to aspirin, long-term use of non-aspirin NSAIDs was not associated with a reduced risk of developing breast cancer in our study.…”
Section: Discussioncontrasting
confidence: 51%
“…Among the four studies that previously reported an estimate for non-aspirin NSAIDs, two of them found a negative result (Egan et al, 1996;Johnson et al, 2002) and the other two studies found a suggestion of a slight risk reduction (Coogan et al, 1999;Cotterchio et al, 2001). The summary estimate for these studies is 0.89 (0.79 -1.01) (González-Pérez et al, 2003). In our study, the indication among long-term users of aspirin was predominantly cardiovascular prevention.…”
Section: Discussionmentioning
confidence: 55%
“…No evidence of a dose-response relationship was found and some studies indicated that coxibs were also associated with a lower risk of breast cancer [8]. This large-scale meta-analysis is consistent with several smaller meta-analyses [9][10][11][12].…”
Section: Introductionsupporting
confidence: 83%
“…Of the two that focused solely on lung cancer, aspirin users were found to have a significant 27% lower risk in one (Khuder et al, 2005) and a nonsignificant 9% lower risk in the other (Hernandez-Diaz and Rodriguez, 2007). In two other meta-analyses in which lung cancer was embedded in a wider review of many cancers, the first reported a 16% lower risk for aspirin users that was compatible with no effect or a slightly reduced risk (Gonzalez-Perez et al, 2003), and the other, limited to cohort studies, reported no association (Bosetti et al, 2006). In general, these meta-analyses concluded that a chemopreventive value of aspirin for lung cancer should be interpreted with caution owing to the limitations of the available studies and the heterogeneity of study designs and results.…”
mentioning
confidence: 99%